2016
DOI: 10.1073/pnas.1604180113
|View full text |Cite
|
Sign up to set email alerts
|

Rational design and validation of a vanilloid-sensitive TRPV2 ion channel

Abstract: Vanilloids activation of TRPV1 represents an excellent model system of ligand-gated ion channels. Recent studies using cryo-electron microcopy (cryo-EM), computational analysis, and functional quantification revealed the location of capsaicin-binding site and critical residues mediating ligand-binding and channel activation. Based on these new findings, here we have successfully introduced high-affinity binding of capsaicin and resiniferatoxin to the vanilloid-insensitive TRPV2 channel, using a rationally desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 68 publications
6
55
0
Order By: Relevance
“…28 ). Moreover, the vanilloid-insensitive TRPV2 channel can be transformed into the vanilloid-sensitive channel by modification of four critical residues in this vanilloid-binding pocket 31,32 . One of these residues is located on the S3 helix: for mouse TRPV1, it is a polar Ser513, and for mouse TRPV2, it is a hydrophobic Phe467 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 ). Moreover, the vanilloid-insensitive TRPV2 channel can be transformed into the vanilloid-sensitive channel by modification of four critical residues in this vanilloid-binding pocket 31,32 . One of these residues is located on the S3 helix: for mouse TRPV1, it is a polar Ser513, and for mouse TRPV2, it is a hydrophobic Phe467 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Changing TRPV2 Phe467 to Ser467 facilitates capsaicin entering into the vanilloid-binding pocket of TRPV2 (refs. 31,32 ). Changing TRPV1 Ser513 to Tyr513, a residue that is equally as bulky as Phe467 in TRPV2, diminishes TRPV1 activation by capsaicin 31,32 .…”
Section: Resultsmentioning
confidence: 99%
“…The S4-S5 linker forms a horizontal helix connecting the peripheral S1-S4 domain to the central pore domain 22 . Recent studies confirmed that it serves a critical role in coupling capsaicin binding to channel activation [16][17][18][19] . We made a series of insertions of 2-to-12 amino acids in length into this key structure, at three different positions (Fig.…”
Section: Functional Tests Of Insertion Mutantsmentioning
confidence: 88%
“…Among TRPV1 stimulations, the capsaicin-channel interaction is the best-understood case in both location and detailed atomic interactions [14][15][16][17][18][19] . None of the functional insertion mutations disrupted capsaicin activation, in agreement with the notion that capsaicin-activation machinery mostly resides within the transmembrane region.…”
Section: Discussionmentioning
confidence: 99%
“…Rosetta has previously been successfully used to calculate gating charges (Khalili-Araghi et al, 2010), simulate voltagesensor movements (Decaen et al, 2008(Decaen et al, , 2009(Decaen et al, , 2011YarovYarovoy et al, 2012;Tuluc et al, 2016), construct open and closed state conformations of Kv channels (Yarov-Yarovoy et al, 2006a;Pathak et al, 2007), and model the interactions of scorpion toxins with voltage-gated Na 1 channels (Cestèle et al, 2006;Wang et al, 2011;Zhang et al, 2011Zhang et al, , 2012. More recently, Rosetta has been used to simulate the access and binding of local anesthetics and anticonvulsants to Na 1 channels (Boiteux et al, 2014), study the interaction of capsaicin with the TRPV1 channel (Yang et al, 2015), and rationally design a vanilloid-sensitive TRPV2 channel (Yang et al, 2016). Similarly, the KCa3.1 structural models we developed in our current study accurately identified key residues for binding of several small molecule probes and explain their atomistic mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%